Patient-derived organoids: a promising tool for breast cancer research - Shi, Yixin; Guan, Zhanwen; Cai, Gengxi; Nie, Yichu; Zhang, Chuling; Luo, Wei; Liu, Jia (Frontiers in Oncology, 2024)
Breast cancer (BC) is the most prevalent malignancy among women worldwide. Traditional research models such as primary cancer cell and patient-derived tumor xenografts (PDTXs) have limitations. Cancer cells lack a tumor microenvironment (TME) and genetic diversity, whereas PDTXs are expensive and have a time-consuming preparation protocol. Therefore, alternative research models are warranted. Patient-derived organoids (PDOs) are a promising in vitro model. They mimic the TME, gene expression, and cell types of original cancer tissues. PDOs have been successfully developed from various cancers, including BC. In this review, we focused on the value and limitations of PDOs in BC research, including their characteristics and potential in drug development, Tumor microenvironment, Deleted[Editor]